Ultrasound-guided platelet-rich plasma injections for post-traumatic greater occipital neuralgia: study protocol for a pilot randomized controlled trial - Stone, Jacqueline E. (Pilot Feasibility Stud, 2021)
BACKGROUND: Post-traumatic headaches (PTH) are a common sequelae of traumatic brain injury (TBI) and greatly impact patient function and quality of life. Post-traumatic greater occipital neuralgia (GON) is a type of post-traumatic headache. Conventional treatment includes steroid/anesthetic injections which typically alleviate pain but have a short duration of effect. Platelet-rich plasma (PRP) is an emerging biological treatment for numerous degenerative disorders, including peripheral nerve disorders. The primary aim of this pilot study is to evaluate whether a randomized control trial of PRP for the treatment of GON in patients with post-traumatic headaches is feasible in regard to recruitment, adherence, retention, and adherence and adverse events. Exploratory aims include improvement in pain, function, and quality of life in patients with post-traumatic GON receiving PRP compared to steroid/anesthetic and normal saline injections. METHODS: Thirty adults (over 18 years of age) with post-traumatic GON will be randomized into one of three groups: (1) autologous PRP injection, (2) steroid/anesthetic injection (standard care), or (3) placebo injection with normal saline. Injections will be performed to the greater occipital nerve under ultrasound guidance by a trained physician. Daily headache intensity and frequency data will be collected pre-injection and for the duration of the study period. Feasibility will be defined as greater than 30% recruitment, 70% completion of intervention, 70% retention, and less than 2 minor adverse events. Exploratory outcomes will be explored using the Headache Impact Test-6 (HIT-6, a valid and reliable 6-item questionnaire for assessment of the impact of headaches across different diagnostic groups of headaches) and the quality of life in following brain injury questionnaire (QOILIBRI). DISCUSSION: This pilot study will be the first to evaluate the feasibility of PRP as a potential treatment of GON in patients with post-traumatic headache. TRIAL REGISTRATION: ClinicalTrials.gov - NCT04051203 (registered August 9, 2019).